COMMUNITY EMPOWERMENT THROUGH PASAR KAMU (YOUTH BREAKFAST MARKET) IN DENAI LAMA VILLAGE DELI SERDANG REGENCY - Azmi, Ulul; Puspitawati; Supsiloani (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
The purpose of this study is to examine the Youth Creative Breakfast Market (PASAR KAMU) located in Denai Lama Village, Pantai Labu District, Deli Serdang Regency, North Sumatra. This study uses a case study approach. The object of this study is the Youth Creative Breakfast Market (PASAR KAMU). Data sources consist of individuals directly and indirectly involved in the activity. To collect data, the researcher used several techniques including documentation, observation, and interviews. Data analysis in this study uses an interpretive approach that aims to achieve a comprehensive understanding of facts, data, and phenomena. This study focuses on the community empowerment process carried out in three stages: the discovery of the PASAR KAMU model, capacity transformation, and capability enhancement. The community empowerment program implemented includes tourism awareness education, training in managing PASAR KAMU as a culinary tourism area, traditional musical instrument training, and entrepreneurship training. The empowerment activities carried out by the Area Kawan Lama group for PASAR KAMU volunteers have resulted in an increased entrepreneurial spirit among young people, increased family income, and contributed to the preservation of regional arts and culture, especially performing arts and traditional Javanese and Malay foods.